Ultrafast vibrational relaxation dynamics in XUV-excited polycyclic aromatic hydrocarbon molecules - Boyer, Alexie; Hervé, M.; Despré, Victor; Castellanos Nash, P.; Loriot, V.; Marciniak, A.; Tielens, A. G. G. M.; Kuleff, Alexander I.; Lépine, F. (Physical review. X, Expanding access, 2021)
Unraveling ultrafast molecular processes initiated by energetic radiation provides direct information on the chemical evolution under extreme conditions. A prominent example is interstellar media where complex molecules such as polycyclic aromatic hydrocarbons (PAHs) are excited by energetic photons. Until recently, ultrafast dynamics following such excitations remained largely unexplored due to the lack of relevant technologies. Here, we use time-resolved mass spectrometry combining ultrashort femtosecond XUV and IR pulses, to investigate the dynamics induced by high-energy photon excitation in PAHs. We demonstrate that excited cations relax through a progressive loss of vibrational selectivity, created at the early-stage dynamics, and which represents the first steps of a complete intramolecular vibrational energy redistribution. This process is in competition with the recently revealed correlation-band dynamics. These results might have direct consequences for the development of XUV molecular physics and other fields such as astrochemistry.
Gesehen am 24.12.2021